2011
DOI: 10.1021/ac2007834
|View full text |Cite
|
Sign up to set email alerts
|

Deployment of a Carbon Isotope Ratiometer for the Monitoring of CO2 Sequestration Leakage

Abstract: In an effort to monitor leakage from underground CO(2) storage, a field-deployable analyzer capable of rapidly measuring the CO(2) mixing ratio and δ(13)C values (±0.05 ppm(v) ± 0.2‰, 60 s) was deployed to distinguish between biogenic and fossil CO(2) sources. The analyzer was interfaced with a multiport inlet unit to allow autonomous sampling from multiple locations. The instrument and inlet interface were deployed at the Zero Emissions Research and Technology (ZERT) site (Bozeman, Montana, July 14-22, 2009) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 21 publications
0
56
0
Order By: Relevance
“…35 mL min −1 ) compared to other in situ instruments that need flows of 400 mL min −1 to 1000 mL min −1 (cf. McAlexander et al, 2011;Tuzson et al, 2011;Hammer et al, 2012;Griffith et al, 2012). The consumption, however, is still not comparable to the minimal amounts needed for our classical IRMS systems (Huang et al, 2012), that allows to measure smaller samples.…”
Section: Instrumental Setupmentioning
confidence: 94%
See 1 more Smart Citation
“…35 mL min −1 ) compared to other in situ instruments that need flows of 400 mL min −1 to 1000 mL min −1 (cf. McAlexander et al, 2011;Tuzson et al, 2011;Hammer et al, 2012;Griffith et al, 2012). The consumption, however, is still not comparable to the minimal amounts needed for our classical IRMS systems (Huang et al, 2012), that allows to measure smaller samples.…”
Section: Instrumental Setupmentioning
confidence: 94%
“…For 2 min averages (at a flow of 0.4 L min −1 ) they report it to be better than 0.2 ‰. For an off-axis integrated cavity output spectroscopy (ICOS) instrument, McAlexander et al (2011) report a long-term precision of 0.11 ‰ for 35 min integrals (at a flow of 0.5 L min −1 ). A detailed description and thorough calibration strategy for a Fourier-transform infrared spectroscopy (FTIR) instrument was given by and Hammer et al (2012).…”
Section: F R Vogel Et Al: Evaluation Of a Cavity Ring-down Spectromentioning
confidence: 97%
“…Vogel et al (2013) found a precision 0.2 ‰ with 5 min averaging intervals for a model G1101-i analyzer from Picarro. Guillon et al (2012) and McAlexander et al (2011) found a precision of 0.05 ‰ and 0.15 ‰ with 60 s averaging for two model DLT-100 analyzers from Los Gatos. Bowling et al (2003) showed a precision of 0.25 ‰ with a 2 min sampling interval for a model TGA100 from Campbell Scientific.…”
Section: Precision Of Measurementmentioning
confidence: 98%
“…However, in comparison to IRMS, whose operational procedures are mature, IRIS is a relatively immature technology still subject to a number of artifacts some users may not be fully aware of (Griffith et al, 2012;Werner et al, 2012). Sensitivity to changing environmental conditions (e.g., temperature dependence; Guillon et al, 2012) and dependence of δ 13 C on CO 2 concentration are the two main sources of error affecting the IRIS measurements (Wada et al, 2011;McAlexander et al, 2011;Guillon et al, 2012). Proper calibration is necessary to ensure accurate measurements Kammer et al, 2011;Guillon et al, 2012;Hammer et al, 2013;Vogel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This combination of long effective absorption pathlength, immunity to light intensity noise, as well as the possibility to measure spectra in high spectral resolution makes CRDS an ultrasensitive detection method for all sorts of stable and transient molecules, including CO 2 (Friedrichs 2008;Kerstel and Gianfrani 2008). Recently, easy-to-handle and robust isotope ratio CRDS as well as cavity-enhanced absorption spectroscopy (CEAS) instruments entered the market and have been successfully used to perform isotope selective field measurements on land (Graham et al 2010;Gupta et al 2009;Krevor et al 2010;McAlexander et al 2011) and in coral reefs (Bass et al 2012).…”
mentioning
confidence: 99%